1998
DOI: 10.1097/00006842-199809000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Mindfulness Meditation-Based Stress Reduction Intervention on Rates of Skin Clearing in Patients With Moderate to Severe Psoriasis Undergoing Photo Therapy (UVB) and Photochemotherapy (PUVA)

Abstract: A brief mindfulness meditation-based stress reduction intervention delivered by audiotape during ultraviolet light therapy can increase the rate of resolution of psoriatic lesions in patients with psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
365
1
22

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 636 publications
(401 citation statements)
references
References 35 publications
5
365
1
22
Order By: Relevance
“…Numerous well-controlled studies demonstrated that meditation practice itself can have profound mind/body effects [25, 26, 27, 28 and 29]. In one recent randomized, controlled trial, patients who practiced mindfulness mediation while undergoing ultraviolet light treatments for moderate to severe psoriasis were found to heal at approximately four times the rate of those patients who received ultraviolet treatment alone [28]. In that study, the meditation intervention was delivered by using an audiocassette tape recording in the isolation of a light booth, so social support variables were not present.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous well-controlled studies demonstrated that meditation practice itself can have profound mind/body effects [25, 26, 27, 28 and 29]. In one recent randomized, controlled trial, patients who practiced mindfulness mediation while undergoing ultraviolet light treatments for moderate to severe psoriasis were found to heal at approximately four times the rate of those patients who received ultraviolet treatment alone [28]. In that study, the meditation intervention was delivered by using an audiocassette tape recording in the isolation of a light booth, so social support variables were not present.…”
Section: Discussionmentioning
confidence: 99%
“…Mindfulness-based therapies have been used successfully to treat anxiety disorders (Kabat-Zinn et al, 1992;Miller, et al, 1995) and recurrent depression (Ma and Teasdale, 2004;Segal et al, 2002), as well as compulsive behaviors such as substance abuse and binge eating (Kristeller and Hallett, 1999). Mindfulness has even been shown to help in the treatment of medical conditions such as fibromyalgia (Goldenberg et al, 1994), chronic pain (Kabat-Zinn et al, 1985), and skin diseases (Kabat-Zinn et al, 1998).…”
Section: Empirical Findingsmentioning
confidence: 99%
“…‹majinasyon, meditasyon, kas gevfleme egzersizleri, nefes egzersizleri, bu amaçla kullan›lan tekniklerdir. Bu teknikler, akne, egzema, ürtiker, psoriazis, hiperhidroz ve nörotik ekskoriyasyon gibi dermatolojik hastal›klar›n tedavisinde ilaç tedavilerinin yan›nda etkili bulunmufltur 42,43 .…”
Section: Gevfleme Teknikleriunclassified